Paper‐Based RNase Digestion toward Viral Nucleic Acid Self‐Tests - Georgios Chondrogiannis; Anna Toldrà; Martin Hanze; Mahiar Max Hamedi (Advanced Materials Interfaces)
Abstract Home‐based Nucleic Acid Amplification Tests (NAATs) for viral infections would be an important step to improve public health, but sample preparation remains an important obstacle, particularly for the protection of target RNA from RNases in samples. Here, a new method for RNase deactivation in saliva samples is presented. This method uses Proteinase K (PK) immobilized on nitrocellulose membrane to store and deliver the enzyme, capable of digesting nucleases present in the sample. The immobilized PK is also separated from the amplification reagents, so that it does not disrupt DNA amplification, thus omitting the need for heat‐deactivation or dilution steps. Treatment by PK nitrocellulose at 50 °C dramatically decreases the RNase activity of RNase A, in diluted saliva samples, and even shows promising results at 42 °C. The potential of this method to protect RNA from digestion is further demonstrated, by pretreating diluted saliva samples spiked with Influenza Virus A (IVA) genomic RNA, which allows its amplification and colorimetric detection by lateral flow strips. In the absence of PK pretreatment, the RNA is digested by RNase, which leads to false negative results. These findings show that immobilized PK enables the integration of sample preparation of viral samples toward home‐based NAATs.